Effects of Different Daqu on Microbial Community Domestication and Metabolites in Nongxiang Baijiu Brewing Microecosystem - Mao, Fengjiao; Huang, Jun; Zhou, Rongqing; Qin, Hui; Zhang, Suyi; Cai, Xiaobo; Qiu, Chuanfeng (Frontiers in Microbiology, 2022)
The quality and yield of the fresh Baijiu mainly depend on the activity of pit mud (PM) and the quality of Daqu. However, the cultivation of PM is a long-term process, and high-quality Daqu can change the community structure of fermented grain (FG) and accelerate the evolution of PM communities. The present research aimed to investigate the four different types of Daqu on the FG-fermenting microbial community structure and metabolites and their interphase interactions with PM. These results show that Kroppenstedtia in the bacterial community of Taikong Daqu (TK) was positively correlated with ethyl caproate, which significantly increased the content of FG volatile metabolites, especially lipid components, and facilitated the accelerated evolution of Methanobacteriales and Methanosarcinales in PM. Bacillus has a high relative abundance in Qianghua Daqu (QH), which shows obvious advantages to improving the alcoholic strength of FG and contributing to increasing the abundance of Methanomicrobiales in PM. Qianghua and traditional mixed Daqu (HH) had a similar bacterial composition to QH and a similar fungal composition to traditional Daqu (DZ), and thus also showed the advantage of increased yield but the volatile flavor metabolites produced were not dominant as well as DZ. β-diversity analysis showed that TK fermentation systems in which FG is more likely to domesticate the structure of PM microorganisms. These results indicated that the interaction between microbial communities in various phases of Baijiu fermentation niches was significantly influenced by Daqu. It can not only enhance the key volatiles in FG but also accelerate the direction evolving of the community in PM. Daqu fortified by functional genera or microbiota can evolve a community structure more suitable for Baijiu fermentation. The microbiota composition and interaction between the communities in both Daqu and PM significantly impact the yield and quality of the base liquor.